Digging the Digital: Beat Modalities and the Representation of the Beats in Video Games - Tomasz Sawczuk (European Journal of American Studies)
Ever since setting their foot on the social and cultural landscapes of the post-World War II realities, the Beats have been both the subject of and subject to pop-cultural representations and appropriations. While figurations of Beat sensibility in film, television, press and popular music have been well recognized and analyzed, an area which remains uninvestigated for Beat influences, perhaps due to its relatively short pop-cultural presence, is the one of video games. Recent years, which have marked the release of titles such as Fallout 4 (Bethesda Game Studios, 2015) and Life Is Strange (Square Enix, 2015), attest to a certain amount of interest invested in Beat mythos by both indie game developers and the biggest game studios in the world, thereby opening a new chapter in representing the Beats in visual media. By, on the one hand, mapping out the categories of Beat references in video game narratives and, on the other, setting them against the backdrop of existing models of (mis)appropriating the Beats in visual culture, I will seek to explore the ways in which video game designers venture into the Beat ethos and I wish to address the implications this bears for the lineage of Beat pop-cultural presence. The final part of the essay takes a closer look at Fallout 4, making references to such theoretical concepts as Derridean hauntology, Zygmunt Bauman’s retrotopia and Simon Reynolds’ retromania, to further demonstrate how complex and ambiguous Beat video-game figurations can be.